Faktor-Faktor Penghambat Pemberdayaan Petani Cengkih Di Desa Dolong A Kecamatan Walea Kepulauan Kabupaten Tojo Una-Una - Rifki Firmansyah; Ellys Rachman; Andi Yusuf Katili (Universitas Warmadewa, 2025)
Farmer empowerment should be understood as an effort to enhance the internal capacity of farmers while simultaneously expanding their access to productive resources and business opportunities that can improve their welfare. This research is a descriptive study utilizing a qualitative approach. The objective of this study is to obtain a clear overview of the inhibiting factors in the empowerment of clove farmers by village governments in Tojo Una-Una Regency. Data collection techniques included observation, interviews, and documentation. The research focuses on the role of the village government, capital, and infrastructure. Based on the research findings regarding the role of the village government, it was found that the village government has performed its role appropriately; the government’s role as a facilitator has been implemented well. However, obstacles remain, particularly in the execution of programs planned by the village government. Consequently, cooperation and coordination between the village government and the farming community are required to maximize the needs for collective progress. Regarding capital, the results indicate that the provision and supply of capital by the village government have not been well-implemented due to a lack of planning and limited village budgets. Furthermore, the procurement of infrastructure and facilities by the village government is considered suboptimal due to budget constraints. Increased attention to the procurement and maintenance of infrastructure is a key factor for the successful development of clove farming in various regions. The village government must optimize empowerment efforts, provide information regarding market prices, and conduct counseling and mentoring programs to improve farmer welfare. Providing capital assistance programs for farmers, such as People's Business Credit (KUR), is essential for agricultural productivity to grow and succeed. It is expected that the village government can provide optimal infrastructure to support all forms of agricultural activities so that farming income can be maximized.